2011
DOI: 10.1115/1.4004636
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation and Evaluation of Velocity Fluctuations During Rotating Stall of a Centrifugal Pump

Abstract: Flow instabilities like rotating stall can lead to severe vibrations in turbomachines if the eigenfrequency of the rotor is equal to the stall frequency. The goal of the present work is to shed some light on the origin of the rotating stall phenomenon in a centrifugal pump. The resulting fluctuating loads are quantified using numerical computations. For the chosen configuration transient PIV data are available for validation. In addition to measuring the stall frequency in the stationary frame, the CFD data is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 10 publications
0
39
0
Order By: Relevance
“…Moghaddam [14] presented a numerical simulation to control rotating stalls and surges in jet engine compression systems by using a controller. Lucius [15] evaluated the risk of resonance by analyzing the stall frequency during rotating stalls in a centrifugal pump.…”
Section: Introductionmentioning
confidence: 99%
“…Moghaddam [14] presented a numerical simulation to control rotating stalls and surges in jet engine compression systems by using a controller. Lucius [15] evaluated the risk of resonance by analyzing the stall frequency during rotating stalls in a centrifugal pump.…”
Section: Introductionmentioning
confidence: 99%
“…At off-design conditions, separate flow would develop on blade suction side leading to partial impeller channels being blocked [9]. At low flow rates, especially, the separate flow structure may transfer from one blade channel to the adjacent channel forming rotating stall phenomenon [10]. In centrifugal pump, flow out of impeller interacts with volute tongue periodically due to the limited blade number [11].…”
Section: Introductionmentioning
confidence: 99%
“…Gourdain et al studied the cyclical fluctuation of the parameters such as pressure and velocity inside the compressor at a stall condition [6]. Lucius and Brenner experimentally studied the speed variation of a centrifugal pump in rotating stall stage [7]. Choi et al investigated the effects of fan speed on rotating stall inception; the results showed that, at 60% speed, tip leakage flow spillage occurred successively in the trailing blades of the misstaggered blades [8].…”
Section: Introductionmentioning
confidence: 99%